Permanent mandibular canine with two roots and two root canals: Two case reports - Mohammad Ahmad Alenezi; Abdullah Yousef Al-Hawwas (Wolters Kluwer Medknow Publications, 2016)
The knowledge of root canal system of different human teeth is a "road map" for the successful root canal treatment. Mandibular canine usually contains one root with a single root canal. Two-rooted mandibular canine is rare. This paper describes two cases of root canal therapy of permanent mandibular canine with two root canals and one apical foramen (Type II) in one root and canine with two separated roots. The clinicians must always suspect anatomical varieties and use all the available tools to diagnose and manage their cases.